Evaluación de cinco atrayentes alimenticios para el monitoreo de la mosca de la fruta díptera: tephritidae en el cultivo del mango - Pintado Cedillo, Jorge Luis (2012)
In the experimental farm of St. Agnes School of Agricultural Sciences at the Technical University of Machala in the province of El Oro, was conducted this research: Evaluation of five food attractants for monitoring fruit fly (Diptera: Tephritidae) in the cultivation of the handle. The objectives were: 1. To establish the efficiency of food attractants for capturing fruit flies 2. Determining the duration of each treatment attractive effect 3. Identify the species of fruit flies captured in the study.b The treatments used were two natural food attractants such as mango and guava juice, and three food attractants available in local markets like protein (Buminal) trimeldure and diammonium phosphate, the same as homemade traps were placed in common, made of plastic soda bottles. The experimental design for this research is completely randomized, with 5 treatments and 4 replicates. The variables evaluated were: number of fruit flies captured fly species caught. Duration of effect appealing to the first, second, fourth and seventh days of exposure. The treatments had the best average capture variables were taken and hydrolysed proteins Buminal Trimeldure, the attractive effect of hydrolysed proteins lasted until the seventh day of exposure. Guava juice was placed in an intermediate capture above the mango juice and diammonium phosphate and Time attractive effect was declining for the fourth and seventh day of exposure. The mango juice and diammonium phosphate were placed in position near the bottom with a low efficiency compared to other treatments, the attractive effect of the mango juice was stable, averaging nearly identical during the week, while diammonium phosphate ascending attractant effect was prolonged until the seventh day of exposure. Of the species caught in the research that had the greatest percentage was Anastrepha fraterculus (Wiedemann) with 91% of flies captured. We also found a lower percentage to Anastrepha obliqua (Macquart) with 5%, Anastrepha distincta (Greene) with 3% and Anastrepha striata (Schiner) with 1% of flies captured.